A Method for Calculating Export Supply and Import Demand Elasticities - Tokarick, Stephen (IMF Working Papers; Working Paper ;, 2010)
Trade elasticities are often needed in applied country work for various purposes and this paper describes a method for estimating import demand and export supply elasticities withoutusing econometrics. The paper reports empirical estimates of these elasticities for a large number of low, middle, and upper income countries. One task for which trade elasticities are needed is in developing exchange rate assessments and this paper shows how the estimated elasticities can be used for this purpose.